Analysis of the economic and environmental potential of wind energy use as an alternative source in the Peruvian mining industry - Ticlla Lozada, José Jahir; Velasquez Romero, Luis Fernando; Díaz Díaz, Marco Antonio; Polo Herrera, Kelly Milena (LACCEI, 2025)
Mining is a key economic activity in many countries. However, its high energy consumption and environmental impact raise significant concerns. This study evaluates the feasibility of adopting wind energy as an alternative to conventional energy sources in the Peruvian mining industry. A quantitative approach was employed using a descriptive, non-experimental design to analyze the costs and benefits of this transition and compare greenhouse gas (GHG) emissions from both energy sources. The findings indicate that implementing wind energy presents a significant opportunity for long-term reductions in investment, operational, and maintenance costs. Projections estimate that the San Juan de Marcona wind farm in Peru would require an investment of $342 million, while the Punta Lomitas wind farm would demand $570 million over the same period. Comparatively, electricity costs for mining companies are projected to range between $175.99 million and $2.87 billion over 30 years. Furthermore, the transition to wind energy could reduce between 662,515.2 and 5,999,443.2 tons of CO₂-equivalent emissions over three decades. These findings demonstrate that wind energy is not only an economically viable alternative for the mining sector but also a sustainable solution that contributes to environmental protection and the transition to a cleaner economy.